The Effect of Exercise Therapy on Amyotrophic Lateral Sclerosis Patients: A Literature Review - Nuraini Fikri; Cicilia Febriyani Hayuningrum; Nabila Syawala Parlian; Rasya Rizki Hadi Putra; Gede Ananda Krisna Parama Satya (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Weakness caused by motor neuron degeneration in Amyotrophic lateral sclerosis (ALS) can result in avoidance of physical activity, resulting in deconditioning and decreased health-related quality of life. The literature review that the author obtained from previous research has a role in shaping the character of thinking in this study. The articles used in this study were obtained from three databases, namely PubMed, Science Direct and Google Scholar. The keywords used during the search were ALS, Exercise, Therapy, Exercise Therapy, Amyotrophic Lateral Sclerosis, carried out a maximum of 2019. Out of 10 articles, there are 7 articles stated that aerobic exercise therapy and strength training had a positive effect on ALS. While 3 other articles showed changes but were not significant. The results of this preliminary ALSFRS-R study support the safety and feasibility of 12 sessions of supine whole-body stepping in individuals with ALS. This respiratory EMST training program was well tolerated and resulted in positive changes in respiratory and bulbar function in ALS. Our prospective CPET study measured significantly reduced exercise capacity in ALS via non-invasive CPET. Genetically predicted physical activity was not significantly associated with risk of neurodegenerative disorders. A 12-week combined aerobic and strength training program was significantly superior to freezing alone in improving respiratory function, mobility, and well-being in ambulatory ALS patients.